2020
DOI: 10.1007/s00394-020-02285-2
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of red meat, genetic susceptibility, and risk of LADA and type 2 diabetes

Abstract: Purpose Red meat consumption is positively associated with type 1 (T1D) and type 2 (T2D) diabetes. We investigated if red meat consumption increases the risk of latent autoimmune diabetes in adults (LADA) and T2D, and potential interaction with family history of diabetes (FHD), HLA and TCF7L2 genotypes. Methods Analyses were based on Swedish case–control data comprising incident cases of LADA (n = 465) and T2D (n = 1528) with matched, population-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
0
18
0
2
Order By: Relevance
“…Some studies have reported PRM or URM consumption to be positively associated with T2DM incidence [6][7][8][9][10][11][12][13][14][15][16]. However, other studies have reported an inverse or null association between red meat intake and T2DM incidence [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported PRM or URM consumption to be positively associated with T2DM incidence [6][7][8][9][10][11][12][13][14][15][16]. However, other studies have reported an inverse or null association between red meat intake and T2DM incidence [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…These subgroups will be referred to as LADA high and LADA low . A handful of studies included data on interaction with genetic risk factors, primarily HLA risk genotypes ( 28 , 36 , 40 , 43 , 48 , 50 , 51 ). In these studies, carriers of HLA high risk had genotypes DR3/3, DR3/4, DR4/4, or haplotypes of DR4-DQ8 or DR3-DQ2 and carriers of HLA low/intermediate risk had DR3/X, DR4/X, DRX/X or DR4-DQ7.…”
Section: Lifestyle or Environmental Factorsmentioning
confidence: 99%
“…Estimation of a healthy diet was based on the ''Life's Simple 7" dietary goals [3] including intake of vegetables and fruit (low-risk cut-off: >400 g/day), fish (>2 servings/week), sugarsweetened beverages (<150 g/d, equals 64 kcal), whole-grain (>48 g/d), and sodium (<1.5 g/d). We additionally included consumption of processed red meat (<1 serving/d), because it has recently been associated with increased risk of LADA and type 2 diabetes [22]. Participants were classified into three categories based on the healthy diet score, i.e.…”
Section: Healthy Lifestyle Components and Covariatesmentioning
confidence: 99%
“…LADA also shares features with type 2 diabetes, including adult onset, insulin resistance [9,13] and, according to some studies [14,15] increased frequency of TCF7L2 risk genotypes, which is primarily seen for less autoimmune LADA [16]. Lifestyle factors linked to type 2 diabetes have been associated with LADA [17] including overweight [18] physical inactivity [19,20] diet [21,22] smoking [23] and alcohol consumption [24]. However, to what extent the combination of healthy lifestyle factors may reduce the risk of LADA is not clear; to date only one study, based on few cases and a limited number of lifestyle factors have addressed this issue [25].…”
Section: Introductionmentioning
confidence: 99%